An investigation into the effectiveness of an IT-based learning management system to support learning in a New Zealand primary school - Benson, Jana (Curtin University, 2012)
The major purpose of this study was to investigate the use of an “IT” based Learning Management System to support education in a New Zealand Primary School. Perceptions of teachers, parents and students were gathered through collecting qualitative and quantitative feedback. In order for this to be achieved, surveys/questionnaires were collected and collated and focus group interviews assisted in interpretations of the data for each group of participants.In particular, the TROFLEI was the chosen instrument for the students to complete providing information on their perceived actual and preferred learning environment. The initial validation was conducted with 200 students across two separate schools. Statistical analysis revealed that the TROFLEI was suitable for use in upper primary and was a valid and reliable tool.There were 122 students enrolled in St Mary’s across the Year 5 and 6 year levels and students’ attitude and achievement outcomes were statistically significantly correlated with each of the TROFLEI learning environment scales. Associations were also made according to year levels and gender of students.Focus group interviews allowed for qualitative data to be collected by each group of participants. There were four groups for each of the teachers, parents and students. Gathering data from each of these groups meant that a triangulation of data was sought creating a rich picture of results.The results were categorised into the following themes Perceptions, Technological Changes, Change of Existing Processes and Adapted and Improved Learning Environment. Within each of these themes, findings were presented according to the readiness of participants, improved learning, connections, add on approaches, workload, buy in of participants, potential of the system, competency, functionality, skills, professional development, time, key processes, assessment capabilities, ownership, student voice, reflection, language, paper technology, portfolios, practice, questioning, equity, awareness, experts, different learning styles, involvement, barriers, engagement, progress, change and support.